Microwave-sintering enhanced photovoltaic conversion in polycrystalline Nd-doped BiFeO3. Issue 13 (September 2020) - Chen, Pin-Yi; Chen, Jing-Ren
Abstract: This work reports remarkable photovoltaic effects in the microwave-sintered lead-free perovskite (Bi0.93 Nd0.07 )FeO3 (B7NFO) ceramics with indium tin oxide (ITO) thin film under 405 nm blue irradiation. Maximal power conversion efficiency (PCE) 1.2% and external quantum efficiency (EQE) 17% can be obtained at low irradiation intensity. Optical absorption and photoluminescence emission suggest direct bandgap ( E g ) in the range of 2.11–2.21 eV in B7NFO ceramics. Grain boundaries exhibit a lower electrical potential and higher electrical conductivity, and can act as conduction channels for the photo-generated charge carriers. High-resolution transmission electron microscopy (HR-TEM) suggests that field-enhanced photovoltaic effects are associated with large and highly ordered polar nano-regions (PNRs) in the matrix. Microwave-sintering process corresponds to a lower activation energy (433 kJ/mol) of grain growth than the conventional-sintering process (604 kJ/mol). This study demonstrates that the microwave-sintering process can be an effective and cost-less technique for energy-harvesting polycrystalline materials.